2017
DOI: 10.1007/s10072-017-2942-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive vagus nerve stimulation (nVNS) as symptomatic treatment of migraine in young patients: a preliminary safety study

Abstract: Recent clinical experiences and clinical trials have demonstrated the safety, tolerability, and efficacy of non-invasive vagus nerve stimulation (nVNS; gammaCore) for the acute and prophylactic treatment of migraine. nVNS has a favorable adverse event profile, making it an attractive option for sensitive patient populations. We explored the safety, tolerability, and efficacy of nVNS as acute migraine treatment in adolescents. A group of adolescent patients suffering from migraine without aura were trained to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 13 publications
2
34
0
Order By: Relevance
“…Our findings add to pre-existing evidence for the potential therapeutic value and safety of the preventive and acute use of nVNS as an adjunctive to prophylactic and abortive drugs in EM patients. We observed comparable responsiveness for head pain severity and frequency [9][10][11][12][13][14][15][16][17][18][19] outcome parameter of the PRESTO study and found a higher rate of pain-freedom and pain-relief attacks as well as a higher rate of severity reduction in migraine patients compared to sham stimulation [17]. This meaningful improvement was accompanied by a considerable rescue medication decrease [18].…”
Section: Brief Summary Of Study Findings and Comparison With Availablmentioning
confidence: 63%
See 1 more Smart Citation
“…Our findings add to pre-existing evidence for the potential therapeutic value and safety of the preventive and acute use of nVNS as an adjunctive to prophylactic and abortive drugs in EM patients. We observed comparable responsiveness for head pain severity and frequency [9][10][11][12][13][14][15][16][17][18][19] outcome parameter of the PRESTO study and found a higher rate of pain-freedom and pain-relief attacks as well as a higher rate of severity reduction in migraine patients compared to sham stimulation [17]. This meaningful improvement was accompanied by a considerable rescue medication decrease [18].…”
Section: Brief Summary Of Study Findings and Comparison With Availablmentioning
confidence: 63%
“…However, preventive and abortive pharmacological/behavioral interventions overlap in both migraine subtypes and failed to achieve favorable response in a considerable proportion of migraineurs [6][7][8]. Thus, cervical non-invasive vagus stimulation (nVNS) has been approved to represent a reasonable and safe adjunctive treatment option for prevention and abortive migraine therapy [9][10][11][12][13][14][15][16]. In two RCT trials, the EVENT study (chronic migraine prevention with non-invasive vagus nerve stimulation) and PRESTO study (prospective study of nVNS for the acute treatment of migraine) and several prospective observational cohort studies, nVNS demonstrated the capability to effectively act as adjunctive prophylaxis and rescue intervention in episodic and chronic migraine as well as in associated mood and sleep disturbance [10][11][12][16][17][18][19].…”
mentioning
confidence: 99%
“…A preliminary open-label single-arm safety study in nine adolescents (13-18 years old) EM without aura patients revealed that 46.8% of their treated migraine attacks showed a beneficial result. No device-related AEs were observed [34]. For menstrual/menstrually related migraine patients (n = 56), an open-label non-invasive VNS study as mini-prophylaxis revealed that 39% of the subjects showed 50% or more reduction in headache days.…”
Section: Open-label Studies Of Transcutaneous Vns (The Gammacore® Devmentioning
confidence: 93%
“…Interestingly, in 47% of all nVNS-treated attacks, adjunctive rescue medication was not required and 53% of all attacks required rescue medication. A pain-free state was observed after 1 h of treatment in 40% (19/47) and pain relief was observed in 6% (3/47) 16. Given these facts, nVNS deserves clinical attention as a considerable and safe alternative in migraine subtypes with impaired therapy options like menstrual-related migraine or migraine in young adolescents.…”
Section: Cervical Noninvasive Vns and Primary Headache Disordersmentioning
confidence: 99%